CHARACTERISTICS OF GRAMMAR PROCESSING IN COMPUTER PROCESSING - Bairwa, Ghanshyam; Bairwa, Shriram (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Panini brought all the languages of the world into his mind and formulated the most scientific formulas. There is no doubt that Panini, the teacher was the father of language. Thus, all the newly innovative streams of thought of this fundamental research thesis, combined with the ocean of research, are nectarized by proper churning and are now in the form of my emotionally rich essence. What, then, is the mainstream of research? It is said that— The mainstream of my research is knowledge engineering. Because there, in principle, in the Bhagavad Gita and in the Bhagavad Gita, in practice, the various assistance given by the poor relative and the poor Natha in due course to the poor Pandavas encourages the pursuit of knowledge and science. न हि ज्ञानेन सदृशं पवित्रमिह विद्यते। तत्स्वयं योगसंसिद्धः कालेनात्मनि विन्दति1।। श्रद्धावाँल्लभते ज्ञानं तत्परः संयतेन्द्रियः। ज्ञानंलब्ध्वा परां शान्तिमचिरेणाधिगच्छति2।। अध्याय 4/39 भगवद्गीता For there is nothing holy like knowledge in this world. That is what the perfected yogi himself finds in himself in time. He who is devoted to it and has controlled the senses attains knowledge by faith. Having attained knowledge, he soon attains supreme peace. Chapter 4/39 Bhagavad Gita (The soul knows all the alternative things, as all knowledge is in the world.)